EVALUVATION OF COMPRESSIVE PROPERTIES OF CHOPPED STRAND MAT E- GLASS FIBER REINFORCED EPOXY COMPOSITE - Mathapati, Sudhir S; Mathapati, Shivukumar S (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The advantage of composite materials is strength and stiffness together with light weight. By choosing an appropriate combination of matrix material and reinforcement material, manufacturers can produce a property that exactly matches the requirements for a particular structure. The present works aims to prepare E-glass fiber reinforced composite with variation in volume fraction of glass fiber content like 1%, 2% and 3% with Bisphenol A as matrix material. Compression tests are conducted on the prepared composite. As a final point of view, the experimental results are compared with the FEA results by using analysis software like ANSYS